Football injuries during the World Cup 2002 - Junge, A.; Dvorak, J.; Graf-Baumann, T. (The American Journal of Sports Medicine, 2004)
BACKGROUND: The Federation Internationale de Football Association (FIFA) World Cup is one of the largest, most popular sporting events but is associated with a certain risk of injury for the players. PURPOSE: Analysis of the incidence, circumstances, and characteristics of soccer injury during the World Cup 2002. STUDY DESIGN: Prospective survey. METHODS: The physicians of all participating teams reported all injuries after each match on a standardized injury report form. The response rate was 100%. RESULTS: A total of 171 injuries were reported from the 64 matches, which is equivalent to an incidence of 2.7 injuries per match; approximately 1 to 2 injuries per match resulted in absence from training or match. More than a quarter of all injuries were incurred without contact with another player, and 73% were contact injuries. Half of the contact injuries, or 37% of all injuries, were caused by foul play as rated by the team physician and the injured player. CONCLUSION: The incidence of injuries during the World Cup 2002 was similar to those reported for the World Cup in 1994 and in 1998. Increased awareness of the importance of fair play may assist in the prevention of injury.